2000
DOI: 10.3189/172756500781833061
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of remote-sensing techniques to measure decadal-scale changes of Hofsjökull ice cap, Iceland

Abstract: Dynamic surficial changes and changes in the position of the firn line and the areal extent of Hofsjo« kull ice cap, Iceland, were studied through analysis of a time series (1973^98) of synthetic-aperture radar (SAR) and Landsat data. A digital elevation model of Hofsjo« kull, which was constructed using SAR interferometry, was used to plot the SAR backscatter coefficient (³) vs elevation and air temperature along transects across the ice cap. Seasonal and daily ³ patterns are caused by freezing or thawing of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 41 publications
2
33
0
Order By: Relevance
“…In Brandt et al (2008) and Langley et al (2007), the authors give the backscatter coefficient extent of superimposed ice in C-band co-polarization. However, other authors have suggested that superimposed ice is not distinguishable from the bare ice zone (Casey & Kelly, 2010;Hall et al, 2000;König et al, 2001a). The difficulty in detecting superimposed ice zones complicates the acquisition of the equilibrium line location from remote sensing, which will be discussed below.…”
Section: Radar Glacier Zonesmentioning
confidence: 94%
See 1 more Smart Citation
“…In Brandt et al (2008) and Langley et al (2007), the authors give the backscatter coefficient extent of superimposed ice in C-band co-polarization. However, other authors have suggested that superimposed ice is not distinguishable from the bare ice zone (Casey & Kelly, 2010;Hall et al, 2000;König et al, 2001a). The difficulty in detecting superimposed ice zones complicates the acquisition of the equilibrium line location from remote sensing, which will be discussed below.…”
Section: Radar Glacier Zonesmentioning
confidence: 94%
“…Therefore, the maximum late summer snow line elevations acquired from frequent SAR observations have been used to estimate the equilibrium line, and the closeness of these values suggests a potential use for SAR in complementing traditional in situ equilibrium line monitoring for mountain glaciers (Casey & Kelly, 2010;Smith et al, 1997). However, in a negative mass balance year, the equilibrium line is difficult to detect on SAR images because it is obscured by older firn with similar backscatter coefficients (Hall et al, 2000;Jaenicke et al, 2006).…”
Section: Sar and The Equilibrium Linementioning
confidence: 99%
“…6a). The backscatter signal from the ice is changing seasonally to changes in surface roughness, as melt water is creating a rougher ice surface due to local melt water streams (Shi and Dozier, 1995;Hall et al, 2000) (Fig. 6a, see yellow to orange colors on ice in the melt season, compared to 5 the light blue color in the cold season).…”
Section: Identifying Glacier Faciesmentioning
confidence: 99%
“…The superimposed ice zone has lower backscatter response compared to the firn in the cold season, but higher backscatter than glacier ice, as the ice transmits much of the microwaves (e.g. Langley et al, 2009) and additionally the ice surface are controlled by roughness (Shi and Dozier, 1995;Hall et al, 2000). 20…”
Section: Identifying Glacier Faciesmentioning
confidence: 99%
See 1 more Smart Citation